Informing Game Sense Pedagogy with a Constraints-Led Perspective for Teaching Tennis in Schools (Agora for Physical Education and Sport, 2018)
The Game Sense approach (GSA) helps sport teachers adopt a pedagogical toolkit for the complex interplay of collective decision making in tennis that evolves from the dynamics of momentary configurations of play meeting the personal coordination dynamics of the players. This pedagogical toolkit emphasises game-based play to teach players how to perceive the game as “thinking players” capable of functional behaviours that answer the requirements of momentary configurations of play. This paper, therefore, builds on recent theoretical debate in the areas of skill acquisition, the complementarity of perception-decision making and personal coordination dynamics (techniques), complex learning theory and coaching pedagogy, to connect the constraints-perspective of skill acquisition and the pedagogy of the Game Sense approach to enable theoretically informed tennis teaching. Practical implications of game-based training will be explained using the example of the Tennis for Primary Schools program alignment with the developmental stages of the Australian Curriculum for Health and Physical Education (ACHPE), which are described as student achievement standards in this curriculum.
Keywords: Tennis; games; game sense; sport; teaching; coaching